The Macroeconomic and Social imbalances in the Eurozone in the period of Economic Crisis (2008 - 2014) - Tamourantzis, Asimakis (International Conference on Business and Economics - Hellenic Open University, 2023)
This paper attempts to shed light on the economic and social effects of the economic crisis among Member States of the Eurozone in the period 2008-2014 emphasizing the imperative revision of the framework of the Stability and Growth Pact. Particular emphasis is given to the growing Macroeconomic and Social imbalances between Euro (€) North and Euro (€) South, which had posed a threat to the economic viability and social cohesion in the Eurozone. JEL Classification: D63, E02, E60, E62, H30 Key words: Eurozone crisis, Economic Inequality, Macroeconomic Imbalances, Social Imbalances, Stability and Growth Pact